How do EFL Students Boost Their Self-Confidence in Speaking? - Annisa, Nurul; Ardiana (IKIP Siliwangi, 2025)
This study aims to reveal the strategies used by students to build their confidence in speaking English. In this study, the participants of this study were 11 students from the English Education study program at Universitas Muhammadiyah of Makassar. This research employed a qualitative method, where data was obtained through interviews with participants to explore their experiences and strategies in overcoming anxiety. The results showed that the students used various approaches such as independent practice, the use of audio-visual media, simulations, group discussions, and also the use of gestures. Through these strategies, many students were helped in overcoming anxiety and also made them more confident when speaking in public. Through self-practice, students can expand their vocabulary, improve their pronunciation, and prepare themselves to speak spontaneously in real situations. Meanwhile, the use of audio-visual media such as learning videos and technology-based applications also has a significant impact on supporting the learning process. This research has made an important contribution by highlighting students' active participation in finding ways to build their confidence independently. The research recommends further exploration of the long-term impact of this strategy on students' speaking ability in various contexts.